Comparing wavelet and Fourier perspectives on the decomposition of meridional energy transport into synoptic and planetary components - Heiskanen, Tuomas Ilkka Henrikki; Graversen, Rune Grand; Rydsaa, Johanne Hope; Isachsen, Pål Erik (Quarterly Journal of the Royal Meteorological Society, 2020)
The Arctic region shows some of the world's most significant signs of climate change; for instance, a negative trend in summer sea‐ice cover of around 15% per decade and Arctic amplified surface‐air warming that is three times the global average. The atmospheric energy transport plays an important role in the Arctic climate. Recently a Fourier‐based method for studying the atmospheric energy transport contribution by planetary‐ and synoptic‐scale waves has been proposed. Recent studies based on this method show that planetary waves contribute more than synoptic waves to the atmospheric energy transport into the Arctic. However, this Fourier method suffers from being incapable of resolving spatially localized systems such as cyclones. Here an attempt to evaluate this problem is presented by applying the method on synthetic and reanalysis data. In addition, an alternative method based on a wavelet decomposition is proposed and compared with the Fourier‐based method. The wavelet method is based on localized basis functions which should be capable of resolving these localized systems. The wavelet method shows an impact of synoptic‐scale transport on Arctic temperatures which is not captured by the Fourier method, whilst the planetary‐scale effect of both methods appears similar.